Transmission of respiratory tract infections at mass gathering events - Petersen, E.; Memish, Z.; Zumla, A.; Maani, A. A. (Current Opinion in Pulmonary Medicine, 2020)
Purpose of review: Mass gathering events bring people from across all continents increasing the risk of spread of aerosol transmissible respiratory tract infections. Respiratory tract infections for instance in pilgrims attending the world's largest recurring annual pilgrimage, the Hajj are common. We review recent literature on viral and bacterial infectious diseases with special focus on the Hajj. Recent findings: The prevalence of bacterial and viral infections continue to increase, because of the acquisition of rhinovirus, coronaviruses (229E, HKU1, OC43), influenza A H1N1, Streptococcus pneumoniae, Haemophilus influenzae and Staphylococcus aureus during Hajj. Whilst MERS-CoV continues to circulate in the Middle East, no cases of MERS-CoV have yet been identified in pilgrims during Hajj. Summary: Respiratory tract infections are a major cause of morbidity in pilgrims attending mass gathering events. The management of severe respiratory infections should consider investigation and empirical coverage for the most likely agents based on syndromic surveillance data from hosting country and /or other relevant exposure history during events. Pneumococcal and Pertussis vaccines should be recommended for Hajj pilgrims.